EU emission trading: better job second time around? - Joachim Schleich; Regina Betz; Karoline S. Rogge (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2007)
The EU Emission Trading Scheme (EU ETS) for CO2-emissions from energy and industry installations reflects a paradigm shift towards market-based instruments for environmental policy in the EU. The centerpieces of the EU ETS are National Allocation Plans (NAPs), which individual Member States (MS) design for each phase. NAPs state the total quantity of allowances available in each period (ET-budget) and determine how MS allocate allowances to individual installations. The NAPs thus govern investments and innovation in energy efficient technologies and the energy sector. In terms of distribution, they predetermine winners and losers. In this paper we analyze and evaluate 25 NAPs submitted to the European Commission (EC) for phase 2 (2008-2012) of the EU ETS. At the macro level, we assess whether the submitted ET-budgets are stringent, and whether they imply a cost-efficient split of the required emission reductions between the EU ETS sectors (energy and industry) and the remaining sectors (transportation, tertiary and households). Comparing the submitted ET-budgets with those already approved by the EC suggests that the EC's decisions significantly improved the effectiveness and economic efficiency of the EU ETS. But given the high share of Kyoto Mechanisms companies are allowed to use, the EU ETS is unlikely to require substantial emission reductions within the EU. At the micro level, we assess (across countries and phases) the allocation methods for existing and new installations, for closures and for clean technologies. A comparison of the NAPs for the second phase and the first phase (2005-2007) provides insights into the (limited) adaptability and flexibility of the scheme. The findings provide guidance for the future design of the EU ETS and applications to other sectors and regions.
urn:nbn:de:0011-n-559242
Keywords: 360; Emissionshandel; EU-Umweltpolitik; Allokation; Klimaschutz; Wirtschaftspolitische Wirkungsanalyse; EU-Staaten